Stability and Bioaccessibility of α-tocopherol-enriched Nanoemulsions Containing Different Edible Oils as Carriers - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Academic Press, 2023)
Nanoemulsions have been described as carriers of bioactive compounds since they can protect them during digestion and improve their bioaccessibility. However, their stability and bioaccessibility can be influenced by nanoemulsion composition, mainly by the lipid phase characteristics. Consequently, this study aimed to evaluate three different carrier oils (avocado-AVO, flaxseed-FLA, and chia-CHI) on the stability and bioaccessibility of α-tocopherol carried in nanoemulsions. Particle characteristics (particle size-PS and polydispersity index-PdI) and oxidative stability of nanoemulsions, and α-tocopherol degradation during storage were determined. In addition, free fatty acids (FFAs) release kinetics and α-tocopherol bioaccessibility during in vitro digestion were analyzed. Results showed that all nanoemulsions were colloidally stable due to their droplet characteristics (PS < 200 nm and PdI<0.2), where no phase separation was observed. AVO nanoemulsion was the most stable against oxidation due to its high monounsaturated and saturated fatty acids, while CHI nanoemulsion showed the highest chemical stability of α-tocopherol during storage. Besides, AVO nanoemulsion showed the most significant release of FFA (94%) and the highest α-tocopherol bioaccessibility (81%). In conclusion, the oil type affects the chemical stability and bioaccessibility of α-tocopherol carried in nanoemulsions. Thus, AVO oil can be used as a carrier of fat-soluble vitamins to increase its bioaccessibility during digestion. © 2023 The Authors